Podcasts about Community-based Theater to Strengthen Women’s Land Rights and Entrepreneurship (Darija) - Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2025)
Seeking to challenge these deep-rooted norms, ICARDA, in collaboration with Oxfam and Spect’Act Foundation, introduced ‘Theatre of the Oppressed’, an interactive drama technique pioneered by Brazilian dramatist Augusto Boal. The method encourages audiences to step into the roles of protagonists facing oppression, exploring solutions through improvisation and debate. The Podcasts summarize the approach and findings in Amazigh and Darija.